3D MXene Architectures for Efficient Energy Storage and Conversion - Nicolosi, Valeria; Li, Ke; Liang, Meiying; Coelho, João; Pinilla, Sergio (My University, 2020)
2D transition metal carbides and/or nitrides (MXenes), by virtue of high electrical conductivity, abundant surface functional groups and excellent dispersion in various solvents, are attracting increasing attention and showing competitive performance in energy storage and conversion applications. However, like other 2D materials, MXene nanosheets incline to stack together via van der Waals interactions, which lead to limited number of active sites, sluggish ionic kinetics, and finally ordinary performance of MXene materials/devices. Constructing 2D MXene nanosheets into 3D architectures has been proven to be an effective strategy to reduce restacking, thus providing larger specific surface area, higher porosity, and shorter ion and mass transport distance over normal 1D and 2D structures. In this review, the commonly used strategies for manufacturing 3D MXene architectures (3D MXenes and 3D MXene‐based composites) are summarized, such as template, assembly, 3D printing, and other methods. Special attention is also given to the structure–property relationships of 3D MXene architectures and their applications in electrochemical energy storage and conversion, including supercapacitors, rechargeable batteries, and electrocatalysis. Finally, the authors propose a brief perspective on future opportunities and challenges for 3D MXene architectures/devices.
Keywords: 2D materials; Porous materials; MXene nanosheets; 3D architectures; MXene devices; Energy storage and conversion